2003
DOI: 10.1364/ol.28.000167
|View full text |Cite
|
Sign up to set email alerts
|

Watermarking of three-dimensional objects by digital holography

Abstract: We present an optical method for information watermarking of three-dimensional (3D) objects by digital holography. A hidden image is embedded by double phase encoding in a phase-shift digital hologram of the 3D object. We decode the watermarked hologram to reconstruct the hidden image and the 3D object. We use either the entire hologram or a part of it to decode the hidden image. Experiments are presented to illustrate the ability to recover both the 3D object and the decoded hidden image. Digital holograms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(36 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Digital holography is a technique of hologram recording, processing and reproduction. It can be generated by computer or CCD collection [13]. In recent years, digital holographic technology has been applied to the field of digital watermarking and shows great potential.…”
Section: 3the Digital Holography Technologymentioning
confidence: 99%
“…Digital holography is a technique of hologram recording, processing and reproduction. It can be generated by computer or CCD collection [13]. In recent years, digital holographic technology has been applied to the field of digital watermarking and shows great potential.…”
Section: 3the Digital Holography Technologymentioning
confidence: 99%
“…Image watermarking is an important technology to protect copyright and secret data in the field of information security [1][2][3][4][5][6]. Optical and digital algorithms of image watermarking have been researched and reported in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of digital watermarking has been reported for one-dimensional or two-dimensional images. In some of the studies watermarking of three-dimensional images have also been reported [13,14]. Image watermarking using digital holography have been further investigated by several researchers [1517].…”
Section: Introductionmentioning
confidence: 99%